Esophageal atresia type C with overlapping long upper pouch: A rare variant. (2020) - Negash, Samuel; Girma, Hiwote; Woldeselassie, Hanna Getachew
Highlights: A long upper esophageal pouch extending below T4 level is a rare finding in Esophageal atresia. This type of esophageal atresia creates confusion on the traditional NG tube and x-ray test, leading to diagnostic dilemma. The surgery is technically simpler in this variant with good outcome. Any baby in which the NG tube does not extend below the diaphragm should be considered to have EA until proven otherwise. Abstract: Background: Esophageal atresia is one of the most common pediatric surgical conditions with a high mortality in developing countries. The esophagus and trachea have a complex embryologic development leading to a wide spectrum of esophageal atresia anomalies. Long upper esophageal pouch with distal tracheoesophageal fistula is one of these rare varieties. Only a handful of case reports exist on the subject thus far. Most reports are from low income countries. Case presentation: A neonate referred to our hospital after 2 weeks of life for excessive secretions, persistent respiratory distress and vomiting. Diagnosis of esophageal atresia was overlooked because nasogastric tube was advanced a considerable length. After repeat x-ray and esophagogram, we confirmed the diagnosis of type C esophageal atresia with a long upper esophageal pouch. Due to the dilemma in diagnosis, surgery was delayed after the 3rd week of life. Luckily the child survived even with extremely delayed intervention. Conclusion: Esophageal atresia can have an uncommon presentation which causes confusion in the diagnosis. Physicians need to be aware of its existence to avoid unnecessary delays in the management. Fortunately, this variant generally seems to have a good prognosis.